P-10 Photo making in hospice: Exploring the portraiture experience of day hospice patients. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Mortimer, Amabel; Day, Rebecca; Broom, Kate; Perkins, Paul
Abstract : Research aim: Exploring whether taking part in photographic portraiture helps to restore the transformed self-image often associated with the diagnosis of a life-shortening condition. Background/literature review: There is increasing interest in the use of therapeutic photography, yet no study has documented the experiences of hospice users when portrait photography is offered as a means to consider self-image. Methods: Qualitative methodology: audio-taped semi-structured interviews using a topic guide were conducted with people with life-shortening conditions, staff members and volunteers. Interviews were transcribed and analysed using narrative analysis. Results: Respondents provided insights into how their self-image transformed as a result of being given a life-shortening diagnosis, including experiencing a sense of loss and dissonance. The psychosocial impact of the study provided opportunities for respondents to safely confront these image changes, and improve their quality of life by proactively shaping their own physical and emotional identity. Common features emerged within the participatory process, despite different approaches to creating the photographs. Emphasis was on participants' constructed images representing who they are as a person rather than focussing on their illness. Conclusion: Participants can benefit from photographic self-portraiture in a hospice setting, facilitating an experience of rediscovering the self, which may have been lost or left behind due to illness or interventions. It may underpin a more positive psychological shift towards a healthier attitude towards oneself. Application to hospice practice: As well as the clear patient benefit, use of portrait photography may help professionals see the person a patient was before they became part of the medical system. Practitioners of therapeutic creative interventions need to encourage discussion and engagement with healthcare counterparts when offering activities. This could prevent such interventions from remaining on the periphery of healthcare.